Innovative Financial Inclusion for migrants and refugees living in urban areas: Practical lessons for Southeast Asia from Africa - Tongboonrawd, Baranee (Graduate School of Business (GSB), 2019)
The purpose of this study is to examine the innovative financial inclusion for the under-served urban migrant and refugee population in Thailand, respectively. The increasing number of urban migrants and refugees in Thailand requires innovative financial inclusion and livelihood interventions. Many migrants and refugees do not have access to formal financial services due to their legal documentation, although their demands for financial services still exist and remain unsatisfied. The evidence from Kenya in Africa could provide implications and viable options for Thailand in implementing financial inclusion and livelihood programmes in different ways. Using data from the migrants and refugees residing in Bangkok, Thailand through individual interviews, the discourse and narrative qualitative analytical methods were employed to analyse data. The key findings from this study include financial needs, financial inclusion options, livelihood assets and strategies, financial literacy, as well as the livelihood approaches that can support the wellbeing of urban migrants and refugees in the host countries. The findings also revealed the difference in financial needs between urban migrants and refugees in Thailand due to their unique needs and livelihood goals. The data analysis suggested that the financial inclusion and livelihood interventions in Kenya could be applicable for refugees and migrants in Thailand. The roles of financial technology and innovation also have a positive impact in accelerating the financial inclusion of refugees and migrants. The recommendations from this study can help to create the enabling environments for financial inclusion of migrants and refugees in the urban context of Thailand. A comprehensive needs assessment on livelihoods and financial inclusion could explore the actual needs of the migrant and refugee population in in Thailand. The coaching sessions for new arrival groups of migrants and refugees can help them to adjust their livelihood strategies while residing in the host country. The innovation and technology will promote the cost-effective informal banking and open up employment and economic opportunities. The advocacy for the rights of migrants and refugees should be strengthened, including the legislations regarding basic healthcare and education. With a dramatic increase in migration, a better understanding of urban contexts will help develop workable interventions for financial inclusion of urban displaced persons, eventually building resilience and reducing poverty among migrants and refugees.